Potencial antidepressivo do extrato aquoso de Ilex paraguariensis em roedores: envolvimento do sistema monoaminérgico - Reis, Elizete de Moraes (2017)
Ilex paraguariensis is a plant largely consumed in South America as an infusion known as ―chimarrão‖ or ―mate‖, which shows effects related to its action in the central nervous system. However, little is known about its action on monoaminergic system and possible antidepressant effect. In this study, it was evaluated the possible antidepressant potential of aqueous extract of I. paraguariensis in rats and mice and it was investigated the participation of monoaminergic system. In experiment 1, rats were treated with an aqueous extract of I. paraguariensis in place of drinking water, ad libitum, following the traditional preparation of this beverage. After 24 hours and 4 weeks of treatment, it was carried out the behavioral analyze trough of open field, forced swimming and elevated plus maze test. I. paraguariensis reduced the immobility time on forced swimming test after 24 hours (56%) and 4 weeks (28%) indicating a potential antidepressant effect. As positive control to this experiment, it was added an experimental group receiving selegiline, which also presented a reduction in the immobility time on forced swimming test of about 56%. There are not alterations on the locomotor or anxiogenic activity after 4 weeks of treatment with I. paraguariensis. At the end of 4 weeks of treatment with I. paraguariensis, it was evaluated possible oxidative alterations (lipid peroxidation, vitamin C levels and non-protein thiol levels) and activity of the enzyme monoamine oxidase in the brain of the animals. However, there were no significant changes in these parameters. In the experiment 2, mice were treated with three different concentrations of I. paraguariensis (0.05; 0.1 e 0.2 g/mL) in place of drinking water during 7 days, ad libitum. It was performed the forced swimming, tail suspension and open field test after 24 hours of treatment and 24 hours after the end of experimental period. I. paraguariensis caused a decrease in the immobility time in forced swimming test at three concentrations tested 0,05 g/mL (45%), 0,1 g/mL (48%) e 0, 2 g/mL (41%) after 24 hours and 7 days of the treatment (34%, 22% e 28%, respectively). In the tail suspension test, it was observed a reduction in the immobility time in the concentrations of 0.05 g/mL (56%) and 0.1 g/mL (45%) after 24 hours. No changes were observed in locomotor activity of the animals. To evaluate the involvement of monoaminergic system, mice were pretreated with 3-iodo-L-tyrosine (inhibitor of tyrosine hydroxylase, 100 mg/Kg, i.p., 4 days) or p-chlorophenylalanine methyl ester (inhibitor of tryptophan hydroxylase, 100 mg/Kg, i.p., 4 days) or vehicle. After 3 days of treatment with inhibitors, the animals were treated with the extract aqueous of I. paraguariensis 0.05mg/mL or water and after 24 hours of the treatment, the forced swimming and tail suspension test were evaluated. The pretreatment with 3-iodo-L-tyrosine prevented the decrease in the immobility time in tail suspension test, whereas the pretreatment of mice with p-chlorophenylalanine methyl ester prevented the decrease in the immobility time in forced swimming test, demonstrating the involvement of the monoaminergic system in the potential antidepressant activity of I. paraguariensis.